Comparison between Some Bacteria and Fungi for Biodegradation of Glyphosate Herbicide in some Agriculture Soil in Iraq - Faiza Kadhim Emran (Journal of Global Pharma Technology, 2018)
Glyphosate is a compound used as herbicide in the control and killing of grasses and herbaceous plants. It can be used in agriculture to prepare fields before planting during crop development and after crop harvest. Because of its toxicity to non-target organisms, there is need to decontaminate glyphosate from contaminated soils and bioremediation is a very useful alternative to conventional cleanup methods. The success of this will depend on isolating bacteria and fungi with the ability to degrade glyphosate in a changing environment. The abilities of two bacterial species Aeromonassobraia and Acinitobacter hemolyticus and three fungal species Aspergillu niger, penicilium notatum and Rhizopus sp. to degrade glyphosate herbicide under varying environmental conditions were evaluated in this study. The isolates were screened for glyphosate utilization using mineral salt medium containing glyphosate as carbon source. Two bacterial isolates were tested for their ability to biodegradation of glyphosate in liquid medium identified by Vitek compact system. Three fungal isolates were tested for their ability to biodegradation of glyphosate in liquid medium CzapekDox  and  Potato Dextrose agar (PDA).The two bacterial isolates, Aeromonassobraia and Acinitobacter hemolyticus and three fungal isolates, Penicillium notatum, Aspergillus niger, and Rhizopus sp., showed the capacity to utilize glyphosate efficiently and were therefore used for further biodegradation studies. The optimum conditions (incubation period, temperature) for biodegradation of glyphosate were examined. The obtained results indicated that the best incubation period was after 7 days for Aeromonassobraia while the best incubation period was after 9 days for Acinitobacter hemolyticus in mineral salt medium.  Favorite temperature was 450C for both bacterial isolates. Microbial growth during the study was monitored by measuring the optical density at 660 nm. This study showed that Aeromonassobraia and Acinitobacter hemolyticus exhibited a high capacity to efficiently degrade glyphosate under the environmental conditions studied. The obtained results indicated that the best growth was Aspergillus niger after 15 days while the weak growth was Penicillium notatum after 15 days in Czapek Dox and Potato Dextrose agar (PDA).  Fungal growth during the study was monitored by observed rang density growth. This study showed that Aspergillusniger best capacity to efficiently degrade glyphosate under the 50,100 mg/l. Other concentrations (200,300mg/l) inhibit growth for all fungal isolate. Thus, the organisms can be exploited for biodegradation of glyphosate.Keywords: Bacteria, Fungi, Biodegradation, Glyphosate, Herbicide.